Investigation of arsenate uptake by hydrotalcite at hyperalkaline and elevated temperature conditions - Opiso, Einstine M. (Transactions of the National Academy of Science and Technology, 2011)
Hydrotalcite is known to retain large amounts of anionic species due to its positive charge characteristics. Hence, investigating its role for the retention of long-lived dissolved anionic nuclides during an intrusion scenario in radioactive disposal facilities is necessary. This study examined the Mg-Al type hydrotalcite (Mg6A12(CO3)(OH)16•4(H2O)) (Mg/Al ratio = 2) as possible sorbent of anionic nuclide using arsenate as an analogue. The sorption experiments were carried out at alkaline pH condition (pH 11) and elevated temperature of 75ᵒC to stimulate the intrusion scenario at radioactive waste repositories. Arsenate sorption was conducted during and after hydrotalcite formation. The results showed that hydrotalcite was able to remove more than 90 and 70% of arsenate during and after mineral formation, respectively even in the presence of competing anions. The co-precipitated arsenic was more resistant to release and showed a significant irreversible fraction of sorbed arsenate of more than 30%, which could be attributed to the inner sphere complexation with the Mg or Al in the octahedral sheets by displacing their coordinated hydroxyl group and stronger interlayer fixation. Overall, the immobilization of arsenate by hydrotalcite could possibly ensure the long-term immobilization anionic nuclides. Hence, controlling the pore water chemistry of cement to ensure the significant precipitation of hydrotalcite durig hydration must e considered in cementitious systems used in geological waste repositories.